Hydrogen sulfide protects against toxicant acrolein-induced ferroptotic cell death in Sertoli cells - Mao, Zhimin; Ji, Qun; Chen, Ping; Zhong, Kun; Zeng, Xuhui (Frontiers in Pharmacology, 2024)
Acrolein (ACR) is a ubiquitous environmental pollutant and byproduct of lipid peroxidation that has been implicated in male infertility. However, the molecular mechanisms underlying ACR-induced toxicity in Sertoli cells remain unclear. Given its role in inducing oxidative stress, we examined whether ferroptosis, an iron-dependent form of regulated cell death, could mediate ACR toxicity in Sertoli cells. We also tested if hydrogen sulfide (H2S), which has antioxidant and ACR detoxifying properties, could protect Sertoli cells from ACR-induced ferroptosis. ACR exposure decreased Sertoli cell viability, increased protein carbonylation and p38 MAPK phosphorylation, indicating oxidative injury. ACR also depleted glutathione (GSH), downregulated the cystine importer SLC7A11, increased intracellular ferrous iron (Fe 2+ ) and lipid peroxidation, suggesting activation of ferroptosis. Consistently, the ferroptosis inhibitor deferoxamine (DFO) markedly attenuates ACR-induced cell death. Further studies revealed that ACR-induced ferroptotic changes were prevented by exogenous H2S and exaggerated by inhibition of endogenous H2S production. Furthermore, H2S also suppressed GPX4 inhibitor RSL3-induced intracellular ACR accumulation and ferroptosis. In summary, our study demonstrates that ACR induces ferroptotic cell death in Sertoli cells, which can be prevented by H2S through multiple mechanisms. Targeting the H2S pathway may represent a therapeutic strategy to mitigate ACR-induced Sertoli cell injury and preserve male fertility.